Analysis of human saliva metabolome by direct immersion solid-phase microextraction LC and benchtop orbitrap MS. (April 2013) - Bessonneau, Vincent; Bojko, Barbara; Pawliszyn, Janusz
Background: Saliva samples collected from one 58 year old male and one 35 year old female during 7 days of fasting were analyzed by direct immersion of both C18 and mixed-mode biocompatible solid-phase microextraction fibers, in combination with a LC–MS method using a benchtop orbitrap instrument in both positive and negative ionization modes, in order to evaluate the difference in terms of metabolite coverage.Results: The mixed-mode coating provided better results, with the simultaneous extraction of a higher number of both hydrophilic and hydrophobic metabolites. The ability of detected features to distinguish differences between the individuals and changes in saliva metabolome induced by diet was also demonstrated.Conclusion: Saliva may be useful for medical diagnostics as it is non-invasive. The use of biocompatible solid-phase microextraction fibers can play an important role as an alternative sample preparation method for untargeted LC–MS metabolomics studies on human saliva because it provides simultaneous extraction of metabolites with a wide range of polarity, thus allowing the detection of changes in metabolic pathways with unsupervised statistical analyses.